IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 19 TAHUN 2018 TENTANG PENINGKATAN KUALITAS LAYANAN ADMINISTRASI KEPENDUDUKAN DALAM PELAYANAN KTP ELEKTRONIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PONTIANAK - Lale Fernanda Oktaviana (JPASDEV : Journal of Public Administration and Sociology of Development, 2021)
The implementation of Electronic ID Cards in their services indicate problems such as low data accuracy, not covering good governance and e-government, not in accordance with Standard Operating Procedures and service innovations that have not been effective and satisfactory in the field. The focus of this research is aimed at the effectiveness of the Electronic ID Card service which aims to determine the effectiveness of the electronic ID Card service using effectiveness measurements according to Duncan’s three approaches, namely goal achieving, integration, and adaptation. The research method uses a descriptive method as well as a qualitative approach. The location of the research was carried out at The Pontianak Agency of Population Administration and Civil Registry with data collection techniques using observation, interviews, and documentation. The data validity technique refers to the triangulation technique and the data analysis technique using an interactive model according to Miles and Huberman. In the data analysis stage, it shows that the effectiveness of the electronic ID card service has been carried out using an approach to achieving goals, integration, and adaptation. In addition, in its implementation there are inhibiting factors and supporting factors for the effectiveness of the implementation. The effectiveness of electronic ID card services is a form of improving service quality as well as a manifestation of good governance and e-government through the application of good governance principles and the achievement of e-government development. The conclusion of this research is the achievement of measuring effectiveness coupled with inhibiting and supporting factors as well as the realization of the implementation and development of good governance and e-government. then its hoped that service will be maximized if a special application for population administration services and civil registration is made and the availability of a ball pick-up service complaint container is expected and the number of facilities for the elderly and pregnant women is expected to be increased.. Keywords : Effectiveness, Good Governance, e-government